Bahasa Dan Konsep Kebahasaan Dalam Muqodimah Karya Ibnu Khaldun (1332 M – 1406 M) - Erfan Gazali (Indonesian Journal of Arabic Studies, 2019)
This research aims to describe Ibn Khaldun's ideas on the concepts of language that he wrote in his great work 'al-muqaddima'. A review of this ideas using Gadamer's philosophical hermeneutic approach. This paper is descriptive, analytical, interpretative and comparative-synthesis. Interpretation is used to provide an explanation of the thought of Ibn Khaldun based on the understanding of researcher in interpreting the texts of al-muqodimah. The comparative-synthesis aspect is carried out to compare Ibn Khaldun's linguistic ideas with modern linguistic concepts, with the aim of finding a common point of ideas between Ibn Khaldun and modern linguistic theories. Some concepts of Ibn Khaldun language that apparently have similarities with modern language ideas are: lughah, ifÄdah al-kalÄm, fi'l lisÄni, malakah, al-qoshd, fitrah, etc.